Spontaneous Renal Artery Dissection in a Normotensive Young Male - John A. Taylor; Eric C. Martin; Ihor S. Sawczuk (The Scientific World Journal)
We report a case of spontaneous superior pole renal artery dissection in a healthy forty-one year old man. Spontaneous renal artery dissection is a rare event occurring in patients with hypertension or renovascular disease such as fibromuscular dysplasia. This case demonstrates the importance of maintaining renovascular accidents as part of the differential diagnosis of abdominal pain.